2014
DOI: 10.1016/j.trf.2013.10.010
|View full text |Cite
|
Sign up to set email alerts
|

Does the effect of traffic calming measures endure over time? – A simulator study on the influence of gates

Abstract: Accident statistics show that transitions from rural to urban areas are accident prone locations. Inappropriate speed and mental underload have been identified as important causal factors on such transitions. A variety of traffic calming measures (TCM) near rural-urban transitions has been tested in field experiments and driving simulator studies. Simulator experiments where drivers are exposed a single TCM in one session are well reported in the literature. However, the extents to which drivers' behavior will… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 31 publications
0
13
2
Order By: Relevance
“…Ariën et al [23] investigated the effect of gateways on rural-urban transitions from several viewpoints. Firstly, the effect on the driving behaviour, and secondly, effective distance of the measures.…”
Section: Efficiency Of Gatewaysmentioning
confidence: 99%
“…Ariën et al [23] investigated the effect of gateways on rural-urban transitions from several viewpoints. Firstly, the effect on the driving behaviour, and secondly, effective distance of the measures.…”
Section: Efficiency Of Gatewaysmentioning
confidence: 99%
“…The study was conducted using the advanced driving simulator of the Department of Engineering-Roma Tre University. Several studies have demonstrated that driving simulators are useful tools for the evaluation of the driver's behavior induced by the road configuration [42][43][44][45][46][47][48][49][50][51][52][53]. Moreover, driving simulators are ideal tools for studies whose field survey is made impossible by the implicit high risks that the experimenters would be subjected to and the difficulty of ensuring controlled experimentation conditions.…”
Section: Driving Simulator Experimentsmentioning
confidence: 99%
“…Among the different speed-related parameters known in the literature, mean speed is very often used as measure for safe driving, mainly because elevated crash risk and severity have been related to an increase in mean speed (Ariën et al 2013). Other speed related efficiency parameters are 85 th percentile speed, standard deviation of longitudinal acceleration and deceleration, percentage of drivers exceeding the speed limit, the highest speeds, 10 mph pace (Ariën et al 2013(Ariën et al , 2014Corkle et al 2002;Mountain et al 2005). Among other commonly used TCM efficiency parameters are reduction of traffic volume, change in the number of fatal and injury accidents, traffic noise level, vehicle emission and public health impact (Čygaitė et al 2014;Huang, Cynecki 2001;Lee et al 2013).…”
Section: Unified Methodology For Estimating Efficiency Of Traffic Calmentioning
confidence: 99%